An oncofetal antigen, IMP-3-derived long peptides induce immune responses of both helper T cells and CTLs. (2nd June 2016) - Hirayama, Masatoshi; Tomita, Yusuke; Yuno, Akira; Tsukamoto, Hirotake; Senju, Satoru; Imamura, Yuya; Sayem, Mohammad Abu; Irie, Atsushi; Yoshitake, Yoshihiro; Fukuma, Daiki; Shinohara, Masanori; Hamada, Akinobu; et al.
ABSTRACT: Insulin-like growth factor II mRNA-binding protein 3 (IMP-3), an oncofetal antigen identified using genome-wide cDNA microarray analyses, is overexpressed in several malignancies. IMP-3-derived cytotoxic T lymphocyte (CTL) epitopes have been used for peptide-based immunotherapies against various cancers. In addition to CTLs, induction of tumor-associated antigen (TAA)-specific helper T (Th) cells is crucial for establishment of effective antitumor immunity. In this study, we aimed to identify IMP-3-derived long peptides (IMP-3-LPs) carrying CTL and promiscuous Th-cell epitopes for use in cancer immunotherapy. IMP-3-derived Th-cell epitopes that bind to multiple HLA-class II molecules were predicted by in silico analysis, and their immunogenicity was determined by utilizing human T cells. We identified two highly immunogenic IMP-3-LPs presented by multiple HLA-class II molecules. One of the IMP-3-LPs encompassed two CTL epitopes that have been used for peptide-vaccine immunotherapy in ongoing clinical trials. IMP-3-LPs-specific Th cells responded to autologous dendritic cells (DCs) loaded with the recombinant IMP-3 proteins, suggesting that these s (LPs) can be naturally processed and presented. The IMP-3-LPs and specific Th cells augmented the expansion of IMP-3-specific CTLs, which was further enhanced by programmed cell death-1 (PD-1) blockade. In addition, IMP-3-LP encapsulated in liposomes was efficiently cross-presented in vitro, and this LP successfully cross-primed CTLs in HLA-A2 transgenic mice (Tgm) in vivo . Furthermore, one of the IMP-3-LPs induced IMP-3-specific Th cells from peripheral blood mononuclear cells (PBMCs) of head-and-neck malignant tumor (HNMT) patients. These findings suggest the potential usefulness of IMP-3-LPs in propagating both Th cells and CTLs and may have implications for IMP-3-LPs-based cancer immunotherapy.